Transanal total mesorectal excision (taTME) for cancer located in the lower rectum: Short- and mid-term results. Issue 4 (April 2015) - Muratore, A.; Mellano, A.; Marsanic, P.; De Simone, M.
Abstract Background Laparoscopic trans-abdominal total mesorectal excision is technically demanding. Transanal Total Mesorectal Excision (taTME) is a new technique which seems to provide technical advantages. This study describes the results of taTME in a consecutive series of patients with low rectal cancer. Methods From January 2012 to December 2013, a consecutive series of 26 patients with low rectal cancer underwent laparoscopic taTME with coloanal anastomosis. cT4 or Type II-III rectal cancer (according to Rullier's classification) were contraindications to taTME. After anal sleeve mucosectomy, the rectal wall was transected at the ano-rectal junction. A single-access multichannel port was inserted in the anal canal. taTME was performed from down to up until the sacral promontory posteriorly and the Pouch of Douglas anteriorly were reached. A laparoscopic trans-abdominal approach was used to complete the left colon mobilization. Results Sixteen patients (61.5%) were male. The mean distance of the rectal cancer from the anal verge was 4.4 cm (range 3–6). Nineteen patients (73.1%) received long-course neoadjuvant radiotherapy. At final pathology, resection margins were negative in all the patients: the mean distal and radial resection margins were 19 mm and 11.2 mm, respectively. TME was complete in 23 patients (88.5%) and nearly complete in three. Postoperative mortality was 3.8%. The overall morbidity rate was 26.9% (7 patients): two patients (7.7%) had an anastomotic leakage (Dindo I-d). After a mean follow up of 23 months, no patients have developed a local recurrence. Conclusions laparoscopic taTME allow wide resection margins and good quality TME.